ELEMENTS OF RAT TESTES UNDER THE INFLUENCE OF INSECTICIDE ROVIKURT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The purpose of the study was to study the characteristics of the response of germ and somatic cells to the action of rovicurt, as well as to study some aspects of the mechanism of this action.